Secondary school students Green chemistry experiment, knowledge, attitude and practice: instrument development and an exploratory study in Malaysia - Hafsah Taha (Tanjong Malim, 2019)
Secondary school students Green chemistry experiment, knowledge, attitude and practice: instrument development and an exploratory study in Malaysia by Hafsah Taha